Cloud Computing: New Business Opportunities for Telecommunications Companies? - Philip Koehler; Jan Kraemer; Arun Anandasivam (International Telecommunications Society (ITS), 2010)
Cloud computing has recently shifted into the center of attention of Telecommuications Companies. Deutsche Telekom, for example, just announced the importance of cloud computing as one of their leading growth sectors (Deutsche Telekom Press Release, 2010). Also other important telecommunication players such as AT&T, Vodafone and Telefónica are expanding their cloud computing business. Clearly, these developments indicate that telcos believe that cloud computing provides significant business opportunities, particularly by further driving the convergence of telecommunications and information technology. Some researchers, however (cf. Greelan, 2009) state that cloud computing is nothing more than a marketing buzzword. On the other hand, Weiss (2007) mentions that although cloud computing "is a buzzword almost designed to be vague, [it] is more than just a lot of fog". In an effort to shed more light on this debate, we investigate the business opportunities of cloud computing for telecommunication companies in more detail. Thereby, we focus especially on the factors that might especially qualify telcos in becoming a significant player in this emerging domain. More specifically, our contribution is twofold: First, we indentify technical and economic factors that are relevant for the telcos' competitive position in the cloud computing market. Second, we identify future scenarios on how telcos position themselves in this market.
Keywords: L86; L96; M31; 330; Cloud Computing; Telecommunications; Conjoint Analysis